2008
DOI: 10.1007/s12134-008-0062-z
|View full text |Cite
|
Sign up to set email alerts
|

Immigration Debate in Canada: How Newspapers Reported, 1996–2004

Abstract: Media representations shape public opinion of immigration, affect policy debate, and influence immigration law. This paper examines media coverage of immigration in the context of the development and conception of the Canadian 2002 Immigration and Refugee Protection Act. The paper performs a topoi analysis on a data set of 490 articles published in five prominent Canadian English-language daily newspapers that address aspects of immigration law. The results reveal that danger is the most frequent and a relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 16 publications
1
37
0
6
Order By: Relevance
“…Policy documents issued by CIC are a vehicle for elites to construct national interests and national belonging. Our analysis examines how media represents, transmits and, at times, critiques political discourse, while simultaneously upholding the ideological investments of elites (Bauder 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Policy documents issued by CIC are a vehicle for elites to construct national interests and national belonging. Our analysis examines how media represents, transmits and, at times, critiques political discourse, while simultaneously upholding the ideological investments of elites (Bauder 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, there are many possible 'frames' to every story. Research has shown that cultural climate, economic interests and political contestation determine which frame becomes dominant (Scheufele 1999;van Gorp 2005;Bauder 2008aBauder , 2008bHorsti 2008;Matthes and Kohring 2008). Frames are especially pertinent in policy contexts, where they organize consent and legitimation.…”
Section: Expandingmentioning
confidence: 99%
“…In research on problematizations of migration, four topoi have been identified (Bauder 2008a(Bauder , 2008b: economic, humanitarian, endangering and cultural. Cutting across the topoi is the portrayal of migrant men as a threat and women as victims (Schrover 2009(Schrover , 2010b.…”
Section: Expandingmentioning
confidence: 99%
“…In a Canadian context, danger and fear have been the dominant aspect of the debate leading up to immigration policy reform (Bauder, 2008b).…”
Section: Bradimore and Bauder Tamil Refugee Migration In Newsprint Mediamentioning
confidence: 99%